الكفالة بالأجرة وتطبيقها من قبل الهيئة الماليزية لتأمين الودائع لبرنامج التكافل وحماية الفوائد = Guarantee with fee and its application by the Malaysian deposit insurance authority for the takaful and interest protection - Saleh, Abdulmajid Obaid Hasan; Mohd Noor, Azman; Rohman, Ghifary Duyufur; Akbar, Kieren (International Shari’ah Research Academy for Islamic Finance (ISRA), INCEIF University, 2024)
برنامج التكافل وحماية الفوائد التأمينية هو برنامج ابتكاري لحماية المستهلكين الماليين؛ قدمته الهيئة الماليزية لتأمين الودائع لتوفير شهادات التكافل ووثائق التأمين لأصحابها، مع حماية صريحة ضد أي فقدان جزئي أو كلي لفوائدهم في حالة فشل أحد أعضاء التأمين. الهدف الرئيس من برنامج التكافل وحماية الفوائد التأمينية تعزيزُ الثقة العامة في النظام المالي الماليزي، وذلك بحماية أصحاب شهادات التكافل ووثائق التأمين من فقدان فوائدهم. ستقوم هذه الدراسة الأولية بفحص امتثال أداة الكفالة بالأجرة لأحكام الشريعة الإسلامية، واستكشاف أدوات بديلة ممكنة تكون متوافقة مع مبادئ الشريعة. وجميع الانتقادات والاقتراحات في هذا المقال هي جزء من البحث والتدريب الأكاديميين؛ لتحسين صناعة المالية الإسلامية بطريقة إيجابية وبناءة، على أمل أن يفتح المقال الآفاق للباحثين للمضي قدما في أدوات تعزيز الثقة في النظام المالي الماليزي. ***** The Takaful and Insurance Benefit Protection Program is an innovative financial consumer program introduced by the Malaysian Deposit Insurance Corporation to provide takaful certificates and insurance documents to their holders with explicit protection against partial or complete loss of their benefits in case of the failure of an insurance member. The main objective of the Takaful and Insurance Benefits Protection Program is to enhance public trust in the Malaysian financial system by safeguarding the holders of takaful certificate and insurance documents from the loss of their benefits. This preliminary study will examine the Sharīʿah compliance of the guarantee for a fee instrument and explore other possible alternative instruments that comply with Sharīʿah principles. All criticisms and suggestions in the article are considered part of academic exercises to improve the Islamic financial industry positively and constructively, with the hope that the article will encourage participants to express their opinions to develop the industry.